Changes in cortical oscillations linked to multisensory modulation of nociception. Issue 5 (6th December 2012) - Mancini, Flavia; Longo, Matthew R.; Canzoneri, Elisa; Vallar, Giuseppe; Haggard, Patrick
Abstract Pain can be modulated by several contextual factors. For example, simply viewing one's own body can reduce pain, suggesting that the visual context may influence the processing of nociceptive stimuli. We studied changes in electroencephalographic (EEG) oscillatory activity related to visual modulation of nociception, comparing cortical oscillations during innocuous or noxious contact heat, while participants viewed either their own hand or a neutral object at the same location. Viewing the body compared with viewing the object reduced the intensity ratings of noxious stimuli, but not of innocuous heat. Time–frequency analysis of EEG data revealed that noxious, as opposed to warm, stimulation was associated with reduced beta (15–25 Hz) power. Classically, such decreases in oscillatory power indicate increases in sensory cortical activation. These event‐related oscillatory changes were moreover modulated by the visual context; viewing one's own body increased noxious stimulation‐induced beta oscillatory activity bilaterally, relative to viewing a neutral object, possibly indicating inhibition of cortical nociceptive processing. These results demonstrate that visual–nociceptive interactions involve changes in sensorimotor EEG rhythms.